Some Critical Issues for Injection Molding 2012
DOI: 10.5772/34969
|View full text |Cite
|
Sign up to set email alerts
|

Wick Debinding - An Effective Way of Solving Problems in the Debinding Process of Powder Injection Molding

Abstract: Some Critical Issues for Injection Molding 90 1990) or wick-debinding. A wicking agent can be in the form of a porous solid substrate plate or in the form of a loose powder or granulate. The granular form offers a gentle physical support for samples, regardless of their shape, and thus prevents certain flaws, such as distortion and cracking. The capillary extraction is uniform over the entire surface of the green body, which ensures that debinded parts also have, as much as possible, a uniform structure after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…When the optimized debinding program is used, the exothermic peak can be reduced significantly and a more continuous loss of mass can be observed during the debinding stage, as shown in Figure 5(b). The optimized debinding program is characterized by slower heating rates and additional dwell times for a gentler binder removal, which mitigates the aforementioned formation of defects (Gorjan, 2012). The final mass loss of the samples was 19.0 Figure 5 I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the optimized debinding program is used, the exothermic peak can be reduced significantly and a more continuous loss of mass can be observed during the debinding stage, as shown in Figure 5(b). The optimized debinding program is characterized by slower heating rates and additional dwell times for a gentler binder removal, which mitigates the aforementioned formation of defects (Gorjan, 2012). The final mass loss of the samples was 19.0 Figure 5 I).…”
Section: Resultsmentioning
confidence: 99%
“…Partial debinding with a solvent or supercritical fluid can be used to avoid structural defects in the ceramic parts (Chartier et al, 1995). Alternatively, debinding in a powder bed (PB) can be used, where the capillary forces in action extract the liquid binder components and any decomposition products with a low viscosity from the part (Gorjan, 2012;Gorjan et al, 2015Gorjan et al, , 2017Trunec and Cihlar, 2002), a process also referred to as wicking.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal debinding was running at the temperature 550 °C and hold for 3 hours then continued with the heating up to 700 °C at the 0.5 °C/min in order to remove the binder palm stearin from the mold sample. A slow heating rate was applied based on Gorjan [10] who reported that the successful debinding process is commonly achieved by applying a very low heating rate. As a result, the binder decomposed gradually and the removed binder was eradicated and extracted to the surrounding embedment of alumina powder through the capillary forces.…”
Section: Thermal Debinding and Sintering Processmentioning
confidence: 99%
“…Debinding steps are then employed to extract the organic matrix, which constitutes 30 vol% to 60 vol% of the part. This processing step is critical and the selection of debinding routes has been extensively reviewed in the literature [ 8 , 9 , 10 ]. In order to favor shape retention, and to prevent defect creation, low molar mass binder is first removed via solvent extraction.…”
Section: Introductionmentioning
confidence: 99%